Enhancing the performance of 3-phase induction motors by developing a 40-degree asymmetrical coil design for the stator coil - Zuriman Anthony; Refdinal Nazir; Muhammad Imran Hamid (Institute of Advanced Engineering and Science, 2026)
The use of three-phase induction motors in industry is very widespread due to their durability, simplicity, cost, and ease of use. These motors are continuously developed to improve performance. However, the increase in motor performance is directly proportional to the increase in the motor’s cost. Therefore, innovative solutions are needed to make three-phase induction motors more efficient without raising the motor’s price. The study’s goal is to create a motor coil design that won’t cost a lot more but will make 3-phase induction motors more efficient. This study developed a 2-layer coil design with a pair of poles for each layer. The second coil layer is located 40 electrical degrees away from the first layer. In the lab, the motor’s performance was assessed and compared to a conventional motor. This new motor uses identical materials as the conventional model; therefore, it does not incur additional costs. The results showed that this method could increase the rotor speed, output power, efficiency, and load torque of the motor by 0.21%, 16.29%, 15.90%, and 16.05%, respectively.